Karakter Perempuan dalam Novel Penari dari Serdang Karya Yudhistira Andi Noegraha Massardi - Ibnu Hajar; Kasih Kristina Waruwu; Kristiawan Indriyanto (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study analyzes the depiction of the characterization of female characters and perspectives presented through the study of socialist feminism on the novel Dancer from Serdang by Yudhistira Andi Noegraha Massardi. As literary research, this research includes a qualitative descriptive approach with the perspective of feminism as a frame of thought. The novel Dancer from Serdang is the source of data for this study, and the data is obtained through reading, recording, data reduction techniques before conducting descriptive analytical analysis. In collecting data, researchers use data collection in certain parts to facilitate the research carried out. The author concludes that in the novel studied the existence of women in the social environment is quite prominent because the efforts to achieve women in terms of education, economy, and so on can be realized and can be seen from the form of freedom of opinion, rejecting something that is not in accordance with her expectations.